Introduction to the special issue: Studying school choice in Canada - Lubienski, Christopher; Yoon, Ee-Seul (Education Policy Analysis Archives, 2017)
In this article, we introduce the special issue that illuminates issues in school choice and education marketization in contemporary Canada. We begin with a discussion of the proliferation of market models across the globe and the kind of questions that have arisen as public policymakers, philanthropists, and other private interests have embraced and advanced market-oriented reforms. Then we turn to Canada, and briefly discuss the scholarly literature on education privatization and school choice in the past two decades. After that, we present the five articles, highlighting how each piece contributes to a deeper understanding of the changing landscape of choice and competition, as well as how these changes impact schools and communities in a diverse, multicultural country. We conclude by discussing the importance of continuing empirical research in order to inform important debates about how to best meet the needs of the students in a democratic society.